Epidemiological and clinical peculiarities of polyglandular syndrome type 3 in pediatric age - Mariella Valenzise; Tommaso Aversa; Angiola Saccomanno; Filippo De Luca; Giuseppina Salzano (BMC, 2017)
Abstract Background Although the autoimmune polyglandular syndrome type 3 (APS-3) is the commonest APS that may be encountered in pediatric age, last year literature includes only few studies aiming to specifically ascertain the clinical spectrum of APS-3 in childhood and adolescence. Aims of these study were: a) to ascertain how many young patients with apparently isolated Hashimoto's thyroiditis (HT) are at risk of manifesting other autoimmune disorders (ADs) compatible with APS-3; b) to individuate the ADs which most frequently segregate with HT in the context of an APS-3. Methods A selected population of 211 young patients with HT and no risk factors for other APSs was investigated, in order to evaluate the prevalence of other ADs apart from HT and to individuate the ADs which most frequently cluster with HT in the context of APS-3. Results The majority of our patients (70.2%) was found to be affected by no other ADs apart from HT, whereas the remaining 29.8% were classified as affected by an APS-3. The ADs which were found most frequently in aggregation with HT were type 1 diabetes mellitus T1DM (61.9%) and celiac disease CD (22.2%). Conclusions 1) About 30% of young patients with HT may exhibit a clinical picture consistent with APS-3; 2) In the context of APS-3 the ADs that most frequently cluster with HT are T1DM and CD.